UMPSA and PDRM strengthen strategic collaboration - Saharudin, Ramli (UMPSA, 2025)
KUANTAN, 2 January 2025 – The Pahang Contingent Police Headquarters (IPK) witnessed a historic event that reinforced the strategic collaboration between the Royal Malaysia Police (PDRM) and Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).